Doing Business in Nigeria 2014 : Understanding Business Regulations for Small and Medium-Size Enterprises - World Bank (Washington, DC, 2015)
Nigeria accounts for nearly one-fourth of Sub-Saharan Africa s population and is the seventh most populous country in the world. As of April 2014 it is recognized as the continent s largest economy. Ranking 13th in the world for its oil production, Nigeria is Africa s largest producer and holds the second highest proven oil reserves on the continent, after Libya.3 Since embarking on the path of democracy in 1999, the country has enjoyed consistent and high economic growth rates, in the range of 6-8 percent annually in recent years. With its large reserves of human capital and natural resources, a large domestic market, and strong economic fundamentals, Nigeria is well positioned to join the group of large emerging markets and be the continent s powerhouse. Nigeria has already been identified as one of the promising MINT economies (an acronym for Mexico, Indonesia, Nigeria and Turkey), following the BRICs on the path to develop rapidly. Creating jobs to improve the well-being of all Nigerians, regardless of their personal circumstances and location, is a key component of the country s development agenda set out in Vision 20:2020. Good governance and effective institutions at the federal and state levels are critical to strengthening a business climate that encourages inclusive growth. Nigeria s 36 states and Abuja, Federal Capital Territory (FCT) operates with a high degree of autonomy. Without commensurate reforms by state governments, the macroeconomic and institutional reforms of the federal government cannot produce the desired impact to create employment and reduce poverty.